Characterization and Phylogenetic Analysis of the First Complete Mitochondrial Genome of Gnathophyllum americanum (Guérin-Méneville, 1855) (Malacostraca: Decapoda: Palaemonidae) - Chia-Hsuan Sung; Chen-Cheng Cheng; Chang-Wen Huang; Liang-Jong Wang (Fishes, 2023)
Complete mitochondrial genome (mitogenome) sequences can provide useful and varied information for evolutionary and phylogenetic studies. We report the first complete mitogenome sequence of the bumblebee shrimp (Gnathophyllum americanum). The mitogenome is 15,842 bp in length and contains 13 protein-encoding genes, 2 ribosomal RNA genes, and 22 transfer RNA genes. The nucleotide composition of the mitogenome was as follows: A,36.72%; T,29.62%; C,21.0%; and G,12.66%. The most common start and stop codons are ATG and TAA, respectively. The MGO (mitochondrial gene order) of G. americanum and Hymenocera picta is unique in Decapoda. Both the phylogeny based on mitochondrial genomic DNA data and the unique MGO pattern indicate that the genus Gnathophyllum might be a sister genus to the genus Hymenocera. The mitogenomic sequence data obtained in this study will provide more information on G. americanum for species identification, population genetics, and biogeography.